The Relationship Modelling of Advertising, Electronic Word of Mouth and Brand Awareness on Fashion Product Purchasing Decision - Widayat; Nursakinah; Widjaya, Rahmad (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2022)
The consumer behavior of fashion products in online shops is becoming an exciting topic to be re-investigated, because the dynamics and volatility in time-dependent the fashion industry. This study examines the structural relationship model of the influence of advertising variables, Electronic Word of Mouth, and brand awareness on Fashion Product Purchase Decisions with a quantitative approach through a survey of consumers of fashion products in Indonesia. A selection of 250 people was selected by purposive non-probability sampling. Data were collected using a self-administered questionnaire, which has been a validity and reliability test. The collected data were analyzed by Covariance Based Structural Equation Modeling (CB-SEM) employee the AMOS software. Data processing succeeded in constructing a model that met the Goodness of Fit requirements (RMSEA= 0.082 GFI=0.929 TLI=0.935, CFI=0.961, and Hoelter0.05=117). The developed model shows that Advertising and Electronic Word of Mouth (e-WOM) significantly affect purchasing decisions for fashion products. Furthermore, brand Awareness can substantially mediate the influence of advertising and electronic word of mouth on fashion product purchasing decisions